Asyndese? Zum Problem einer 'negativen' Kategorie - Breuer, Astrid Yvonne (Slavistische Beitraege, 2002)
After presenting the theoretical background (Chapter 3.0 to Chapter 3.5), this work critically questions the extent to which sentence combinations, commonly referred to as "non - conjunctive", are characterized by the still common description modes "Zero - connected" and "Connective ellipse" can be detected effectively (chapter 3.6 and chapter 3.7.). At the same time, properties are elaborated that support the later categorial location of the various links.